Electrical Adaptiveness and Electromechanical Response in Gel Composites of Carbon Nanomaterials. Issue 23 (7th November 2018) - Park, Chiyoung; Lee, Seoung‐Ki
Abstract: Mechanosensation is a critical life mechanism. Therefore, it has received much attention in recent years for diverse applications from wearable to biomedical devices. Recently, composite strain sensors composed of a polymer matrix and carbon nanomaterials have been extensively investigated using various processing methods, but mostly use elastic matrices. In general, the sensor sensitivity relies on the tunneling resistance or the ratio of the tunneling resistance to the total resistance of the sensor. In this minireview, we have described the working principles of strain sensors and the preparation of gel composites with carbon nanomaterials as conductive nanofillers. In particular, we emphasized the effects of viscoelastic polymer matrices in composite strain sensors, which have not been well investigated. Abstract : The sixth sense : composite strain sensors composed of a polymer matrix and carbon nanomaterials have been extensively investigated using various processing methods. This review paper describes the preparation of gel composites of carbon nanomaterials for electromechanical sensors and emphasizes the role of viscoelastic matrix for the mechanosensation.